Women on Wheels: empowering women through an innovative training and employment programme. Issue 2 (17th February 2017) - Baruah, Bipasha
ABSTRACT: Significant victories have been won due to the development sector's engagement with gender inequality as a political project, but regressive shifts have also led to development being conceptualised as a managerial issue rather than as a process of social change. This article uses empirical research conducted in New Delhi, India with an organisation that trains and employs poor urban women as commercial drivers to discuss how an obsession with "cost effectiveness" and "scale" can delegitimise the valuable work of some organisations. This article encourages re-engagement with gender equality as a complicated social issue rather than as a technical-rational management project.